Psicologia e religião: uma análise da produção em psicologia e a orientação aos padres quanto à situação de morte - Camara, Sergio Lucas (2017)
Considering the studies on death in the field of psychology, the relationship between psychology and religion and the continuous action of Catholic priests in situations of finitude, this study had the objective of carrying out a systematic and critical review of the production of psychology in Brazil, articulating the themes of death with religion, especially the Catholic Christianity. Researches were performed on the BVS-PSi Platform, integrated to Scielo, from 2011 to 2016, and papers published in Qualis/CAPES A1, A2, B1 and B2 journals were selected, originally written in Portuguese, published in Brazil, having at least one psychologist among the authors. According to the established criteria, only six articles were selected. Of these, none of them explored the religious or spiritual dimension in dealing with death, although the theme had emerged in the researches. The collected material was submitted to analysis, according to three categories: identification characteristics, methodological characteristics and content characteristics. A survey was also made with the documents of the Catholic Church with reference to the formation and guidance to priests, regarding death and dying. The results obtained on psychology production revealed a low number of published articles which link death to religion, and even when it appears in the articles on death/mourning, the theme of religion/spirituality is not explored. Likewise, the articles on religion/spirituality in psychology did not explore the subject of death/mourning. Nevertheless, we have identified significant possibilities of articulation between psychology and religion in the situation of death. With specific reference to Catholicism, the articles produced in psychology are depleted of knowledge about the three moments organized by Catholic Christianity to deal with death and dying. On the other hand, the guidance of the Church to the priests regarding the situation of death is more significant in the organization of rituals, but without references to the advances of production in psychology, which evidences the need for the religious formation to approach the psychological knowledge. In the field of psychology, this research exposes a gap in the studies that articulate death/mourning with religion/spirituality, especially regarding the Catholic Christianity, which counts with the adhesion of a considerable portion of the Brazilian population. Therefore, this research suggests more exploratory studies that appropriate the importance of religion in, at least, two perspectives: expansion of psychological knowledge and clinical practice with mourners. The partnership between religion and psychology can therefore benefit the performance of both psychologists and priests in dealing with the situation of death